(3GdeQehRGJ GdYTQhfs - (3CHh GdeYGdj GdeXaQ Hf eMeO GdeXaQ GdHGZfhj GdTjQGRjs ((3Ydi Hf eSYhO Hf GdeUfa s)
(3ChdgG (B:s
(3SHMGfc Gddge hHMeOc CeG HYO agPg efGaKGJ YLjHI heKGafGJ ZQjHI heQehRGJ TQjaI heSGeQGJ dWjaI jGQH gH dfG ef CeQfG QTOkG hGLYd eYhfJc GdMSfi dfG eOOkG s
(3BNQgG (B:s
(3hVefJgG WdHi hCKfjJ Ydjc adG JLYdfi ef GdNGFfjf jG ef jYde MhGFL GdYGdejf HMb eMeO hBdg GdWjHjf GdWGgQjf CLeYjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1658s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs